DAMPAK KEBIJAKAN PENGEMBANGAN PARIWISATA BAGI MASYARAKAT KELURAHAN WOLOAN SATU UTARA KECAMATAN TOMOHON BARAT - Johanis Turambi; FLORENCE DAICY LENGKONG; NOVVA PLANGITEN (Sam Ratulangi University, 2023)
ABSTRACT This research is a descriptive research with a qualitative approach, the data collection technique of this research is using the observation method, namely, direct observation of the research location, as well as conducting interviews and documentation. As for the aim of the researchers is to describe how the impact of tourism development policies on the people in the North Woloan Satu village. Based on the results of research on the impact of existing tourism development policies in the Woloan Satu Utara sub-district, that tourism development policies have a good impact on the community, where through these policies the community can improve the economy, can open jobs for people around tourism areas. Keywords: Policy, Develomentp, Tourism